Re-thinking and re-positioning 'being in the moment' within a continuum of moments: introducing a new conceptual framework for dementia studies. Issue 3 (4th March 2022) - Keady, John David; Campbell, Sarah; Clark, Andrew; Dowlen, Robyn; Elvish, Ruth; Jones, Lesley; Kindell, Jackie; Swarbrick, Caroline; Williams, Sion
Abstract: This article draws upon six social research studies completed by members of the Dementia and Ageing Research Team at The University of Manchester and their associated networks over an eight-year period (2011–2019) with the aim of constructing a definition of 'being in the moment' and situating it within a continuum of moments that could be used to contextualise and frame the lived experience of dementia. Using the approach formulated by Pound et al. (2005 ) in synthesising qualitative studies, we identified this continuum of moments as comprising four sequential and interlinked steps: (a) 'creating the moment', defined as the processes and procedures necessary to enable being in the moment to take place – the time necessary for this to occur can range from fleeting to prolonged; (b) 'being in the moment', which refers to the multi-sensory processes involved in a personal or relational interaction and embodied engagement – being in the moment can be sustained through creativity and flow; (c) 'ending the moment', defined as when a specific moment is disengaged – this can be triggered by the person(s) involved consciously or subconsciously, or caused by a distraction in the environment or suchlike; and (d) 'reliving the moment', which refers to the opportunity for the experience(s) involved in 'being in the moment' to be later remembered and shared, however fragmentary, supported or full the recall.